Fe(III)/l-Valine-Catalyzed One-Pot Synthesis of N-Sulfinyl- and N-Sulfonylimines via Oxidative Cascade Reaction of Alcohols with Sulfinamides or Sulfonamides - Zhang, Guofu; Xing, Yunzhe; Xu, Shengjun; Ding, Chengrong; Shan, Shang (Synlett, 2018)
An efficient Fe(III), l-valine, and 4-OH-TEMPO catalytic system was found for the oxidation of alcohols followed by condensation with sulfinamide or sulfonamide in one pot for the synthesis of N-sulfinyl- and N-sulfonylimines compounds under mild conditions. This transformation accommodates a variety of substrates, shows high functional-group tolerance, and affords the corresponding products in good to excellent yields.
Keywords: Fe catalysis; one-pot; N-sulfinylimines; N-sulfonylimines; oxidative cascade; alcohols